“The guests were arriving at the dacha...”: on the dacha topos in the poetry of Alexander Kushner - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The topos of the dacha – like the topos of the city (St. Petersburg) and that of the garden – is an important element of the spatial dimension of Alexander Kushner’s poetic world. The article attempts to trace the productivity and functionality of the topos in selected texts of this contemporary poet. Attention is drawn to the characteristics of the categories of time and space, the constituents of the life on the dacha , as well as connections with the literary tradition. When taking up the subject, Kushner updates the rich semantics of the topos: the dacha as a place of retreat for a poet, a place of rest and work, the little homeland, a paradise on Earth.